Influential Factors Shaping Retirement Strategies among Employed Individuals - Ghimire, Dinesh Mani; Pandey, Bikash (Journal of Emerging Management Studies, 2026)
Purpose – This research aims to assess the financial retirement planning strategies of employed individuals in the Kathmandu Valley of Nepal by examining the relationships between financial risk tolerance (FRT), financial self-efficacy (FSE), financial literacy (FL), retirement goal clarity (RGC), and culture on financial planning for retirement (FPR).Design/methodology/approach – Quantitative research approach with explanatory research design was employed to a cross-sectional data, supplemented by correlational analysis to measure the strength of relationships between the variables. The study explores the mediating role of culture in the relationship between RGC and FPR.Results – Findings revealed that FRT, FSE, FL, and RGC significantly and positively influence FPR, with RGC exerting the strongest impact. This underscores the critical role of clear retirement goals in effective financial planning.Conclusion – The study concluded that employed individuals predominantly rely on retirement goal clarity when formulating retirement planning strategies.Implications – Theoretically, this research provides a foundation for further exploration of the financial, cognitive, and behavioral factors influencing retirement planning within the Nepali context. Economically, it highlights the necessity for individuals to prioritize retirement goal clarity in their financial strategies.Originality/value – This paper is significant in the Nepali research landscape, as it is among the few studies to investigate financial retirement planning, focusing on the roles of FRT, FSE, FL, RGC, and culture in shaping individuals' financial planning behaviors.